Efficacy and Safety of Bushenjiangya-Optimized Granule for Left Ventricular Diastolic Dysfunction in Hypertensive Patients: A Double-Blind, Randomized, Placebo-Controlled Trial. (19th May 2020) - Gao, Qun; Cui, Xiao-yun; Dong, Fei; Fan, Wen-ying; Li, Pin-hui; Liu, Jing; Lu, Jin-jin; Meng, Yan; Qu, Wen-bai; Zhou, Kun; Lin, Qian
Abstract : Objective . The study aimed to evaluate the efficacy and safety of Bushenjiangya-optimized (BSJYO) granule on left ventricular diastolic dysfunction (LVDD) in hypertensive (HTN) patients. Methods . 120 patients diagnosed with HTN plus LVDD were randomly assigned to the BSJYO granule group and placebo group, and all patients received basal western medicine (WM) treatment. After eight weeks of treatment, we evaluated echocardiography, traditional Chinese medicine (TCM) syndromes, 24-hour ambulatory blood pressure, liver and kidney functions, and adverse events. Major adverse cardiovascular events (MACEs) were collected at 6-month follow-up. Results . Compared with pretreatment, E/Ea (Doppler-derived index of filling pressure and worsening LVDD) significantly decreased significantly after 8 weeks of treatment in the BSJYO granule plus basal WM group (10.52 ± 1.87 vs. 9.49 ± 1.49, P < 0.01 ), alongside reductions in significantly effective response (SER), effective response (ER), and total effective response (TER = SER + ER) in TCM symptom scores (21.59% vs. 71.70%, P < 0.01 ). There were no differences between treatment groups in kidney and liver function, early adverse events, or MACE. Conclusion . BSJYO granule plus basal WM is an effective and safe therapy for HTN patients with LVDD.